Impact of variables of the P-selectin – P-selectin glycoprotein ligand-1 axis on leukocyte-platelet interactions in cardiovascular disease - Gremmel, Thomas; Koppensteiner, Renate; Kaider, Alexandra; Eichelberger, Beate; Mannhalter, Christine; Panzer, Simon (Thrombosis and Haemostasis, 2015)
The formation of leukocyte-platelet aggregates (LPA), through the P-selectin – P-selectin glycoprotein ligand (PSGL)-1 axis, plays a pivotal role in atherothrombosis. In order to investigate the influence of platelet (pP-selectin) and soluble P-selectin (sP-selectin), and of variations in the genes encoding for P-selectin (SELP) and PSGL-1 (SELPLG) on LPA formation, we assessed monocyte (MPA)- and neutrophil-platelet aggregates (NPA) as well as pP-selectin by flow cytometry in 263 patients undergoing angioplasty and stenting. sP-selectin was determined by ELISA, the SELP Pro715 allele and the SELPLG Ile62 allele were determined by allele specific PCR. The Pro715 allele was significantly associated with lower levels of in vivo pP-selectin and sP-selectin, while agonists´ inducible pP-selectin was not influenced by the Pro715 allele. PP-selectin was significantly associated with MPA and NPA formation. The in vivo formation of MPA and NPA depended to 19 % and 7.4 %, respectively, on in vivo pP-selectin, irrespective of the Pro715 allele and the Ile62 allele carrier status. TRAP-6 inducible MPA and NPA depended to 34 % and 27 %, respectively, on TRAP-6 inducible pP-selectin, but were independent of the Pro715 allele carrier status. Carriers of the Ile62 allele showed a stronger correlation between TRAP-6 inducible pP-selectin and TRAP-6 inducible MPA/NPA than non-carriers. Furthermore, TRAP-6 inducible NPA were higher in Ile62 allele carriers, which suggests higher thrombin sensitivity. In conclusion, our findings point to the significant role of pP-selectin for MPA and NPA formation, while other variables like sP-selectin, the SELP Pro715 allele and the SELPLG Ile62 allele have less influence.
Keywords: P-selectin; P-selectin glycoprotein ligand-1; genotyping; leukocyteplatelet interactions